2021
DOI: 10.1007/s00737-021-01145-0
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of maternal depression, anxiety, and stress symptoms from pregnancy to 5 years postpartum in an Australian cohort experiencing adversity

Abstract: The objective of this study is to describe the longitudinal patterns of depression, anxiety, and stress symptoms from pregnancy to 5 years postpartum, in a cohort of Australian mothers experiencing adversity. Longitudinal data were drawn from the control group of a trial of nurse home visiting. Pregnant women experiencing adversity (≥ 2 of 10 adversity risk factors) were recruited from antenatal clinics across 2 Australian states (30 April 2013-29 August 2014. Women completed the Depression Anxiety and Stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 35 publications
5
18
1
Order By: Relevance
“…Moreover, 23 women (9.1%) did not provide any reason. Globally, our retention rate is comparable with those reported by other studies adopting a similar methodology ( 22 , 37 ).…”
Section: Resultssupporting
confidence: 91%
“…Moreover, 23 women (9.1%) did not provide any reason. Globally, our retention rate is comparable with those reported by other studies adopting a similar methodology ( 22 , 37 ).…”
Section: Resultssupporting
confidence: 91%
“…We also found evidence that past mental health (i.e., the pre-pregnancy and pregnancy periods) is associated with postpartum mental health. This result is consistent with longitudinal studies that reported women experiencing depressive symptoms during pregnancy are at high risk of postpartum depression [ 27 , 60 , 61 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings extend on the existing literature by demonstrating the relationship for Australian families experiencing adversity. Notably, families in the current cohort were already less likely to be in paid employment (53%) or have poorer mental health (20–30% with high mental health symptoms, see Bryson et al [ 43 ]) before the pandemic. As such, the relative impacts of the public health restrictions are arguably greater for these families and likely to exacerbate existing health disparities.…”
Section: Discussionmentioning
confidence: 91%